ANALISIS PENGARUH PENDAPATAN DAN BEBAN TERHADAP PAJAK : LABA SEBELUM PAJAK SEBAGAI VARIABEL INTERVENING PADA PT. BANK BENGKULU - Wagini Wagini; Dara Andalas; Karona Cahya Susena (UNIVED Press, 2019)
This study aims to look at the effect of income and burden on taxes with pre-tax profit as an intervening variable. The data used in this study is secondary data in the form of financial statements for the period 2010-2017. Data testing method uses multiple linear regression analysis with t test, F test, and test coefficient of determination. The results showed that income directly had a negative and not significant effect on taxes, with a total effect of -1.400 and a significance level of 5.7%. Whereas indirectly, income has a positive and significant effect on taxes through pre-tax profit as an intervening variable, with a total influence of 1,401 and a level of significance of 0.07%. Direct expenses have a positive and significant effect on taxes, with a total influence of 1,064 with a significance level of 3.6%. Whereas indirectly the burden also has a positive and significant effect on tax with pre-tax profit as an intervening variable, with a total influence of 1,401 with a significance level of 0.07%. The results of the analysis can be concluded that profit before tax is rightly used as an intervening variable to see the effect of income, expense on pre-tax profit because it can contribute influence by 94%. That is, the tax that must be paid by PT. Bank Bengkulu is influenced by three important factors, namely income, expenses and pre-tax profits.